2006
DOI: 10.1681/asn.2006020165
|View full text |Cite
|
Sign up to set email alerts
|

Loss of α3/α4(IV) Collagen from the Glomerular Basement Membrane Induces a Strain-Dependent Isoform Switch to α5α6(IV) Collagen Associated with Longer Renal Survival in Col4a3 −/− Alport Mice

Abstract: Mutations in COL4A3/4/5 genes that affect the normal assembly of the ␣3/4/5(IV) collagen network in the glomerular basement membrane (GBM) cause Alport syndrome. Patients progress to renal failure at variable rates that are determined by the underlying mutation and putative modifier genes. Col4a3 ؊/؊ mice, a model for autosomal recessive Alport syndrome, progress to renal failure significantly slower on the C57BL/6 than on the 129X1/Sv background. Reported here is a novel strain-specific alternative collagen I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
71
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 31 publications
(32 reference statements)
4
71
0
Order By: Relevance
“…13 The immunofluorescence findings of this study were compatible with their result, because we detected type IV collagen ␣5 and 6 chains in the GBM of all KO groups with or without BMT. The GBM deposition of type IV collagen ␣5 and 6 chains increased slightly more in the two BMT groups than in the KO mice, on the basis of the results of immunofluorescence and a Western blot analysis.…”
Section: Discussionsupporting
confidence: 91%
“…13 The immunofluorescence findings of this study were compatible with their result, because we detected type IV collagen ␣5 and 6 chains in the GBM of all KO groups with or without BMT. The GBM deposition of type IV collagen ␣5 and 6 chains increased slightly more in the two BMT groups than in the KO mice, on the basis of the results of immunofluorescence and a Western blot analysis.…”
Section: Discussionsupporting
confidence: 91%
“…C57BL/6 nephrin Y3F/Y3F mice developed a milder and later onset phenotype than CD-1 nephrin Y3F/Y3F mice, and the phenotype was more pronounced in male versus female mice, both of which are consistent with several reports describing strain-and sex-specific differences in the severity of renal disease in genetically modified mice. [24][25][26][27][28][29][30] C57BL/6 nephrin Y3F/Y3F mice showed significant albuminuria at .6 months of age ( Figure 5A). …”
Section: C57bl/6 Nephrin Y3f/y3f Mice Develop Mild Albuminuria and A mentioning
confidence: 99%
“…Recent studies suggested a strain-dependent GBM deposition of ␣5/␣6/␣5 type IV collagen triple helical protomers in the ␣3KO on a C57Bl/6 background yet with almost undetectable levels in the ␣3KO on a 129sv background. 2 Such difference in GBM composition may offer better survival advantage, likely as a result of slower rate of GBM damage because of the presence of type IV collagen molecules (␣5 and ␣6) with better cross-linking capacity. 3 These findings not only highlight the role of type IV collagen specificity in maintaining GBM structure and function but also substantiate the notion that a potential improvement in GBM architecture and renal function can be achieved in Alport renal disease by altering the type IV collagen GBM composition to more stable molecules such as the ␣3 through ␣6 chains.…”
mentioning
confidence: 99%
“…3 These findings not only highlight the role of type IV collagen specificity in maintaining GBM structure and function but also substantiate the notion that a potential improvement in GBM architecture and renal function can be achieved in Alport renal disease by altering the type IV collagen GBM composition to more stable molecules such as the ␣3 through ␣6 chains. 2,3 Indeed, Sugimoto et al 4 along with Prodromidi et al 5 provided evidence for the therapeutic benefit of bone marrow transplantation (BMT) in irradiated ␣3KO mice on the C57Bl/6 background. In contrast to irradiated ␣3KO mice that received ␣3KO bone marrow, the irradiated ␣3KO mice that received wild-type bone marrow revealed significant improvement in GBM architecture associated with de novo expression of ␣3 chain mRNA and protein.…”
mentioning
confidence: 99%